The Politics of Reproductive Ritual - Paige, Jeffery M. (University of California Press, 2021)
""A welcome addition. They argue that rituals of reproduction in preindustrial societies are essentially political. In these societies, they say, men need to control the reproductive power of women in order to establish political power; where there is no law or central government, ritual is used as a way of gaining control. The type of ritual will vary, they conclude, according to the economic base of the society. . . .for those whoa re interested in the subje.